2013
DOI: 10.1111/josh.12048
|View full text |Cite
|
Sign up to set email alerts
|

Is It Bullying or Sexual Harassment? Knowledge, Attitudes, and Professional Development Experiences of Middle School Staff

Abstract: When school administrators fail to provide professional development on both bullying and sexual harassment, staff members do not understand that sexual harassment occurs between students. Thus, they are unaware of policies to protect students from harmful experiences in educational settings and are not likely to understand their own role in preventing them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 26 publications
0
37
0
3
Order By: Relevance
“…This suggests that behavior deemed as sexual harassment may sometimes be intended to express and attract romantic and erotic interest rather than to actually cause distress. Similarly, it has been found that cross-gender bullying, which may to a great extent overlap with behaviors qualifying as sexual harassment (Charmaraman, Jones, Stein, & Espelage, 2013;Shute, Owens, & Slee, 2008), often targets popular children (Sainio, Veenstra, Huitsing, & Samivalli, 2012).…”
Section: Sexuality and Subjection To Harassment And Bullyingmentioning
confidence: 99%
“…This suggests that behavior deemed as sexual harassment may sometimes be intended to express and attract romantic and erotic interest rather than to actually cause distress. Similarly, it has been found that cross-gender bullying, which may to a great extent overlap with behaviors qualifying as sexual harassment (Charmaraman, Jones, Stein, & Espelage, 2013;Shute, Owens, & Slee, 2008), often targets popular children (Sainio, Veenstra, Huitsing, & Samivalli, 2012).…”
Section: Sexuality and Subjection To Harassment And Bullyingmentioning
confidence: 99%
“…To date, most RA and SA prevention efforts have targeted teens through classroom-based education and training (Edwards, Neal, & Rodenhizer-St€ ampfli, 2017). While classroom-based prevention is one component to RA and SA prevention, experts agree that other strategies are needed, including those that target risk and protective factors at outer realms of the social ecological model (DeGue et al, 2012(DeGue et al, , 2014Tharp et al, 2013) and initiatives that engage the important adults in the lives of teens (Charmaraman, Jones, Stein, & Espelage, 2013;Espelage, Low, Polanin, & Brown, 2013;Yoon & Barton, 2008;Yoon & Bauman, 2014).…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…The authors adopted a technique of data triangulation that accomplished breadth, depth, minimized bias, and fostered validity (Leeuwis et al, 2015;Charmaraman et al, 2013). Data arose from different sources employing different data gathering tactics to accomplish data saturation.…”
Section: Methods and Designmentioning
confidence: 99%
“…The choice of teachers as self-reporting research participants stemmed from three motivating factors. (1) The literature gap related to teachersí input in deciphering the bullying dilemma (Charmaraman, Jones, Stein, & Espelage, 2013). (2) Teachers are predisposed to first-hand and secondhand witnessing of bullying as they interact directly with students on almost daily basis.…”
Section: Methods and Designmentioning
confidence: 99%
See 1 more Smart Citation